First case of bacteraemia due to Acinetobacter schindleri harbouring blaNDM-1 in an immunocompromised patient. (January 2018) - Montaña, S.; Palombarani, S.; Carulla, M.; Kunst, A.; Rodriguez, C.H.; Nastro, M.; Vay, C.; Ramirez, M.S.; Almuzara, M.
Abstract: Clinically significant NDM-1-producing Acinetobacter schindleri has not yet been described in the literature. We report the first case of bacteraemia due to an A. schindleri strain harbouring bla NDM-1 recovered from an immunocompromised patient. Our report reinforces the fact that NDM-1 can easily be acquired by Acinetobacter species.